Filtering Effect of Large Rivers on Primate Distribution in the Brazilian Amazonia - Mourthé, Ítalo; Hilário, Renato R.; Carvalho, William D.; Boubli, Jean P. (Frontiers in Ecology and Evolution, 2022)
Over a century after Wallace's proposition of the Riverine Barrier Hypothesis, the role of rivers in the diversification of species remains a matter of interest in Amazon biogeography. Amazonian rivers, in particular those large and fast flowing rivers, are widely recognized to act as barriers to the dispersal of some organisms. However, the extent to which primate species changes across interfluves (β-diversity) in response to river features remains to be explicitly tested. In this study, we examine how river characteristics affect the variation in taxonomic and phylogenetic β-diversity to elucidate the ecological processes behind the differences in primate assemblages between neighboring interfluves in the Brazilian Amazonia. We compiled IUCN distribution maps of 80 river-bounded primate species in 10 interfluves separated by major rivers throughout the Brazilian Amazonia. We assessed both the taxonomic (disregarding phylogenetic relationships between species) and phylogenetic β-diversities. We applied multiple linear models to evaluate whether annual discharge, sinuosity, and reflectance (as a proxy for amount of sediments) in each river or river section that separates neighboring interfluves make rivers effective barriers to primates. We found that mean discharge has a positive effect, while both sinuosity and amount of sediments have negative effects on primate β-diversity. These variables have significant effects on total taxonomic and phylogenetic β-diversity between neighboring interfluves, and their species turnover components. River features however have no effect on species richness differences. Genera are capable of traversing almost all interfluves, but species are replaced by others in opposite interfluves. Discharge affected both small- and large-sized primate total β-diversity, but sinuosity only affected large-sized primate assemblages in neighboring interfluves. Our results indicate that although Amazonian rivers act as barriers for many primate species, this barrier effect seems limited to the short/medium time scales, as primate lineages are able to cross them over long-time scales.